Integrated nutritional care in long-term care: From theory to evidence-based practice - Sonja Lindner-Rabl; Gerhard Wirnsberger; Barbara Bäck; Brigitte Walzl; Karola Putz-Scheicher; Johanna Fabian; Iris Wunder; Elisabeth Derler; Carolin Herzog; Lisa Pieter; Julia Traub; Lutz Kubitschke; et al. (PLoS ONE, 2025)
Against the background of ageing societies and worldwide growing populations with complex care needs, the reorganization of health and social care provision from fragmented towards integrated healthcare is becoming essential. Nutritional challenges, such as malnutrition, are one of the key areas of interest, when redesigning care systems for ageing societies, especially when older people are residing in long-term care. In response to that, this study describes the development of an evidence-based inter-professional nutritional care pathway in long-term care settings. A qualitative multi-method approach of four consecutive sub-processes was performed guided by principles derived from implementation science: 1) Regional maturity assessment, 2) Matching process with existing care pathways, 3) Step-based co-creation with stakeholders, 4) Local implementation, accompanied by a planned multi-level evaluation procedure. The research process resulted in a final nutritional care pathway, structured into seven care episodes leveraging capacity around nutritional care needs of long-term care residents in an inter-professional and person-centered manner. Early evaluation results indicate that the care pathway serves as evidence-based guideline and facilitates resource-efficient practice routines in long-term care. This paper describes an iterative approach to transform nutritional care provision in long-term care. Although the concept was contextualized and developed around local needs and circumstances, it may serve as case example for subsequent integrated care efforts. Further evaluation results are needed to disclose long-term outcomes and effectiveness.